2011
DOI: 10.1093/geronb/gbr058
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Frequency Decline From Midlife to Later Life

Abstract: Results provide evidence for gendered experiences in the sexual life course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 31 publications
4
95
2
1
Order By: Relevance
“…Karraker and colleagues, using a regression decomposition method on data from the National Health and Social Life Survey (NHSLS) and NSHAP, found that women's declining health did not account for a significant portion of sexual frequency decline (Karraker, Delamater, & Schwartz, 2011). Although this is consistent with our findings that chronic illnesses and general health were more clearly linked to sexual activities and functioning in men than women, we did observe that diabetes and fair or poor self-rated health were associated with reduced sexual activity in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Karraker and colleagues, using a regression decomposition method on data from the National Health and Social Life Survey (NHSLS) and NSHAP, found that women's declining health did not account for a significant portion of sexual frequency decline (Karraker, Delamater, & Schwartz, 2011). Although this is consistent with our findings that chronic illnesses and general health were more clearly linked to sexual activities and functioning in men than women, we did observe that diabetes and fair or poor self-rated health were associated with reduced sexual activity in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Older white men have sex less frequently. Frequency does not vary by race for older women (Karraker, DeLamater, & Schwartz, 2011). Education positively predicts older adult sex outcomes (DeLamater & Sill, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…Sexual functioning, activity, interest and satisfaction have been associated with physical benefits such as cardiovascular health, physical benefits of exercise, increased relaxation, and decreased pain sensitivity (Brody, 2010;Chen, Zhan, & Tan, 2009;Jannini, Fischer, Bitzer, & McMahon, 2009). Moreover, health problems of older adults may interfere with their desire for or ability to engage in sexual activities, such as sexual touching and intercourse (Karraker et al, 2011). The link between physical health and sexual activity may explain the observed association between increased age and decreased engagement in partnered sexual activity (Call, Sprecher, & Schwartz, 1995;Galinsky & Waite, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, physical health conditions can be relevant regarding sexual relations and sexual health (Lindau et al, 2007). Physical health affects the capacity of individuals and their partners to engage in sexual activity and mortality influences the availability of sexual partners (Karraker et al, 2011). Additionally, specific conditions, namely, diabetes and hypertension are associated with declines in sexual function (Lindau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%